Two and a half cheers for the national care standards - Kirstie Maclean (Scottish Journal of Residential Child Care)
Nineteen volumes of National Care Standards were issued by the Scottish Executive in the Spring of 2002. The two volumes which are most relevant and important for residential child care owners, staff, children and young people and their parents, are the Standards relating to 'Care Homes for Children and Young People' (Scottish Executive, 2002a) and 'School Care Accommodation Services' (Scottish Executive, 2002b). It is extremely important that units and schools familiarise themselves with the standards and audit their services against them; they are the tool that will be used by the Scottish Commission for the Regulation of Care (the Care Commission) when it registers and inspects services. It is therefore vital that we celebrate the major step forward which the Standards represent for looked after and accommodated children and other children living away from home.